Lipocalin 2 is present in the EAE brain and is modulated by natalizumab - Marques, Fernanda; Mesquita, Sandro D.; Sousa, Joao C.; Coppola, Giovanni; Gao, Fuying; Geschwind, Daniel H.; Columba-cabezas, Sandra; Aloisi, Francesca; Degna, Matilda; Cerqueira, João J.; Sousa, Nuno; Correia-Neves, Margarida; et al. (Frontiers in Cellular Neuroscience, 2012)
Multiple sclerosis (MS) is a demyelinating disease that causes major neurological disability in young adults. A definitive diagnosis at the time of the first episode is still lacking, but since early treatment leads to better prognosis, the search for early biomarkers is needed. Here we characterized the transcriptome of the choroid plexus (CP), which is part of the blood-brain barriers (BBBs) and the major site of cerebrospinal fluid production, in the experimental autoimmune encephalomyelitis (EAE) mouse model of MS. In addition, cerebrospinal fluid samples from two cohorts of patients with MS and with optic neuritis (ON) were analyzed to confirm the clinical relevance of the findings. Genes encoding for adhesion molecules, chemokines and cytokines displayed the most altered expression, supporting the role of CP as a site of immune-brain interaction in MS. The gene encoding for lipocalin 2 was the most up-regulated; notably, the cerebrospinal fluid lipocalin 2 levels coincided with the active phases of the disease. Immunostaining revealed that neutrophils infiltrating the CP were the source of the increased lipocalin 2 expression in this structure. However, within the brain, lipocalin 2 was also detected in astrocytes, particularly in regions typically affected in patients with MS. The increase of lipocalin 2 in the cerebrospinal fluid and in astrocytes was reverted by natalizumab treatment. Most importantly, the results obtained in the murine model were translatable into humans since patients from two different cohorts presented increased cerebrospinal fluid lipocalin 2 levels. The findings support lipocalin 2 as a valuable molecule for the diagnostic/monitoring panel of MS.